BUILDING MAINTENANCE MANAGEMENT SYSTEMS (BMMS): CONTEMPORARY ISSUES IN PROMOTING HEALTHY HOUSING FOR HEALTHFUL LIVING - Anih, P.C.; Awa, K.N (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
Healthy living environment is a product of a well designed maintenance plan. Ignorance and apathy to the efficacies of maintenance management initiatives have resulted in both overt and covert health implications and complications. This study demonstrated the variety of maintenance management systems as addendum to precautionary measure to check the infiltration of building associated diseases. The stl4dy was approached through two major paradigms: the first approach is internalized maintenance management operation where the occupants of the extant facilities were primary participants in the facilities maintenance; the second is externalized maintenance management system where professionals in the field of facilities management or other related fields are involved. The study presented an overview of the basic principles in maintaining and operating various building systems in residential facilities for health and safety. The discussion identified building systems and their components, operating characteristics, and general maintenance practices.